(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective (s): The aim of this study was to find out the correlation between basal serum Follicle Stimulating Hormone (FSH) level, antral follicle count and number of oocytes retrieved during IVF cycle in women with advanced reproductive age. Method: It was a cross sectional observational study which was done between January 2015 and December 2015 in Infertility Management Center, a tertiary center in Dhaka where assisted reproductive technologies are being offered. Eighty nine (89) infertile patients who were between 35 to 45 years of age and have come for IVF treatment for the first time were included in this study. The selected patients had undergone estimation of basal serum FSH by automated immuno assay analyzer and counting of the antral follicles by transvaginal sonography on day two or three. In total sixty nine (69) patients started IVF treatment according to GnRH long agonist protocol. Controlled ovarian stimulation started with 225 IU rFSH. Follicle monitoring was done on day 5 and day 9 and the dosage was kept same or changed according to the patients response. After day nine of stimulation, ten women were excluded as they had no mature follicle of 18 mm or more and cycle was cancelled. So in fifty nine (59) cases ovulation was triggered with hCG 5000 IU on the day when at least one mature follicle measuring 18mm was observed. The ovum pickup was done 32 hours after the trigger and the number of collected oocytes was counted under microscope. Outcome measures of this study was to compare basal FSH and antral follicle count as predictors of ovarian reserve by correlating with the number of oocytes retrieved and to correlate the age of the female partner with the number of oocytes retrieved. Results: Most couples in this study (68.33%) have been suffering from primary infertility and majority of them had six to ten years of infertility. Higher proportion of the female partners (75%) was between 35 to 37 years. The majority of infertile couples have male factor infertility (32%). The second commonest cause found was tubal factor in female partner (20%).Stepwise multiple regression analysis was done. Significant positive correlation was noticed between AFC and number of oocytes (b = 0.2413).There was negative correlation between the basal FSH level and the number of oocytes (b= -0.5083). Age of female partner had weak correlation with ovarian reserve. Conclusion: Measurement of antral follicle number in the follicular phase is a better predictor of ovarian reserve in comparison to basal FSH and age of the women. Bangladesh J Obstet Gynaecol, 2015; Vol. 30(1) : 20-24